2014
DOI: 10.1186/1743-0003-11-132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of range-of-motion and variability in upper body movements between transradial prosthesis users and able-bodied controls when executing goal-oriented tasks

Abstract: BackgroundCurrent upper limb prostheses do not replace the active degrees-of-freedom distal to the elbow inherent to intact physiology. Limited evidence suggests that transradial prosthesis users demonstrate shoulder and trunk movements to compensate for these missing volitional degrees-of-freedom. The purpose of this study was to enhance understanding of the effects of prosthesis use on motor performance by comparing the movement quality of upper body kinematics between transradial prosthesis users and able-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 51 publications
14
77
0
Order By: Relevance
“…When faced with structured multistage manual upper limb tasks, novice prosthesis users have been shown to demonstrate similar trends (Major et al, 2014). During the first few task attempts, variability in the linear acceleration patterns of the forearm is high; however, after practice with the prosthesis, variability has been shown to decrease (Sobuh, 2012).…”
Section: Methods and Analysismentioning
confidence: 96%
“…When faced with structured multistage manual upper limb tasks, novice prosthesis users have been shown to demonstrate similar trends (Major et al, 2014). During the first few task attempts, variability in the linear acceleration patterns of the forearm is high; however, after practice with the prosthesis, variability has been shown to decrease (Sobuh, 2012).…”
Section: Methods and Analysismentioning
confidence: 96%
“…As noted by Hebert et al[5, 6], allowing the subject to choose which blocks to move results in tremendous variability in the trajectories employed, making comparisons among subjects difficult. Previous work [11] has also found that the joint angle ranges and peak angle values observed during the BBT are much lower than those that have been reported from able-bodied subjects performing typical ADLs such as perineal care, drinking from a cup, lifting objects from the ground and off shelves[12], and carton pouring [13]. While it remains difficult to develop a single task that will evaluate every aspect of functional performance, modifications to existing outcome measures may increase their ecological validity, while still maintaining the benefits of ease and speed of implementation; reliable, objective measurement; and repetition of motion.…”
Section: Introductionmentioning
confidence: 93%
“…Although able to restore certain motor functions, these prostheses limit the individual in performing a wide range of tasks useful in the daily living, due to their simple kinematics. Individuals are proficient at compensating for the missing DoFs by changing the motions of their arms and body [2] [3], however, as these compensatory movements often put greater forces on the anatomy, they may result in residual limb pain, secondary musculoskeletal complaints and overuse syndromes [4]- [8]. Hence, more capable and easily controllable prostheses must be designed by engineers for an individual with limb loss, in order to avoid these potential injuries [9].…”
Section: Introductionmentioning
confidence: 99%